Level of Physical Fitness with Physical Education Learning Outcomes - Nawir, Nukhrawi; Amahoru, Nurul Musfira; Ishak, Muhammad (Sains Global Institut, Indonesia, 2023)
The type of research used is regression research to find out: 1) The level of physical fitness of students at SD Negeri Sudirman I Makassar; and 2) The contribution of physical fitness to physical education learning outcomes for students at SD Negeri Sudirman I Makassar. The population of this study was all students at SD Negeri Sudirman I Makassar in grades III, IV, and V, specifically male students, with a sample size of 40 students. The sampling technique is random sampling. The data analysis techniques used are descriptive analysis, data normality test, data linearity test, regression test, and categorization test using the SPSS 20.0 program at a significance level of α0.05. The results of this research show that: 1) The level of physical fitness of students at SD Negeri Sudirman I Makassar is in the Medium category or 72.5%; and 2) Physical fitness has a significant contribution to physical education learning outcomes for students at SD Negeri Sudirman I Makassar, amounting to 69.2%